Determinants of moult haulout phenology and duration in southern elephant seals - Leandri de Kock (Nature Portfolio, 2021)
Abstract Phenological shifts are among the most obvious biological responses to environmental change, yet documented responses for Southern Ocean marine mammals are extremely rare. Marine mammals can respond to environmental changes through phenological flexibility of their life-history events such as breeding and moulting. Southern elephant seals (Mirounga leonina) undergo an obligatory annual moult which involves the rapid shedding of epidermal skin and hair while seals fast ashore. We quantified the timing (phenology) and duration (the time from arrival ashore to departure) of the moult haulout of 4612 female elephant seals at Marion Island over 32 years. Using linear mixed-effects models, we investigated age, breeding state and environmental drivers of moult timing and haulout duration. We found no clear evidence for a temporal shift in moult phenology or its duration. Annual variation in moult arrival date and haulout duration was small relative to age and breeding effects, which explained more than 90% of the variance in moult arrival date and 25% in moult haulout duration. All environmental covariates we tested explained minimal variation in the data. Female elephant seals moulted progressively later as juveniles, but adults age 4 and older had similar moult start dates that depended on the breeding state of the female. In contrast, moult haulout duration was not constant with age among adults, but instead became shorter with increasing age. Moulting is energetically expensive and differences in the moult haulout duration are possibly due to individual variation in body mass and associated metabolizable energy reserves, although other drivers (e.g. hormones) may also be present. Individual-based data on moult arrival dates and haulout duration can be used as auxiliary data in demographic modelling and may be useful proxies of other important biological parameters such as body condition and breeding history.